Psychophysical Impact of COVID-19 Pandemic and Same-Sex Couples’ Conflict: The Mediating Effect of Internalized Sexual Stigma - Pistella, Jessica; Isolani, Stefano; Ioverno, Salvatore; Laghi, Fiorenzo; Baiocco, Roberto (Frontiers in Psychology, 2022)
Research on the effects of the COVID-19 pandemic on same-sex relationships is limited. The present study aimed at analyzing the association between the psychophysical impact of the COVID-19 pandemic and same-sex couples’ conflict, also considering the potential mediating effect of internalized sexual stigma (ISS). For this purpose, psychophysical challenges and couples’ conflict during the COVID-19 pandemic, ISS, age, biological sex, sexual orientation, relationship duration, religiosity, involvement in lesbian, gay, and bisexual (LGB) associations, sexual satisfaction, and interpersonal partner violence were assessed in an Italian sample of 232 LGB people engaged in a same-sex relationship (aged 18–45 years; Mage = 28.68, SD = 6.91). The results indicated that the psychophysical impact of the COVID-19 pandemic was significantly associated with couples’ conflict, and ISS mediated this relationship. Among the covariates considered, only sexual satisfaction was associated with couples’ conflict. The findings suggest that ISS, over and above the adverse effects of the COVID-19 pandemic on psychophysical health, triggered conflict within same-sex relationships. Studying the role of ISS in various relational and social contexts is important, as ISS may have an adverse effect on the mental health of sexual minority people. We recommend that more efforts be made to improve research on the LGB population during the public health response to the COVID-19 emergency, because the paucity of studies underlines the invisibility of this population in many domains, including the domain of romantic relationships. Implications and directions for future research are discussed.